The appropriateness of the title “Papa” used within Neo-Pentecostal Christianity in Zimbabwe: A practical theological reflection - Fenga, Vincent Farirai (Stellenbosch Theological Journal, 2026)
The article challenges the strict boundaries between mentorship and discipleship, advocating for a more integrated theological perspective inspired by Jesus Christ, who seamlessly fulfilled both roles. It places the “Papa” figure within the wider framework of African Cosmologies, drawing connections between prophetic leadership and the traditional role of ancestors as mediators between the divine and humanity. Additionally, the article links this spiritual paternalism to political traditions in Africa, where leaders such as Kwame Nkrumah and Robert Mugabe derived their authority from spiritual sources and were regarded as national patriarchs. By referencing Charles Wanamaker’s Theology in Jesus the Ancestor, the study further investigates the theological foundations of “Papa” and its continuity with messianic figures in the African Initiated Churches (AIC) tradition, such as John Marange and Isaiah Shembe. Ultimately, the article argues that the title “Papa” signifies a theological and cultural convergence of African ancestral mediation, biblical spiritual fatherhood, and centralised prophetic authority, prompting important questions about legitimacy, power, and spiritual accountability in contemporary African Christianity.